Adequacy of knowledge of new medical graduates about diagnosis and management of children and adolescents with type 1 diabetes in a developing country - Abeer Alassaf; Lobna Gharaibeh; Lina Abuna’meh; Rasha Odeh (BMC Medical Education, 2023)
Abstract Background Knowledge of diabetes by the graduate physicians had been reported to be deficient in many aspects of diagnosis and management of type 1 diabetes (T1D). This will reflect on patient care and quality of health services especially in limited-resources countries. Our aim was to assess knowledge of basic management of T1D in new medical graduates in Jordan. Methods A questionnaire was developed to collect information concerning demographics and knowledge and was distributed in paper form and online using google forms. The knowledge was assessed using 28 questions on different aspects of the disease. Results A total of 358 new medicine graduates responded to the survey and female respondents were significantly higher than male respondents. Average number of lectures concerning diabetes during the medical school years was 3.92 ± 1.37. High knowledge scores were on pathophysiology of T1D, hypoglycemia, and certain aspects of diabetic ketoacidosis. Female gender, higher number of persons with T1D the participant had encountered during medical school, and good or excellent expected degree of self-knowledge of diabetes were associated with high knowledge score, p values = 0.01, 0.009, and < 0.001, respectively. Female gender and good or excellent expected degree of knowledge of diabetes predicted high knowledge score, p value = 0.008, and < 0.001, respectively. Conclusion Gaps in knowledge of new medical graduates in certain T1D subjects exist. This can be corrected by many strategies including changes in curricula, elective courses, more clinical exposure, and interprofessional education. These measures must be evaluated for their short and long-term benefits.